POTENSI EKSTRAK TANAMAN OBAT DAN AROMATIK SEBAGAI PENGENDALI KEONG MAS - Wiratno, Wiratno; Rizal, Molide; Laba, I Wayan (Pusat Penelitian dan Pengembangan Perkebunan, 2011)
Potency of Medicinal and Aromatic Crop Extracts to control Golden SnailResearch aimed to evaluate potency of some medicinal and aromatic plants as raw materials of molluscicides to control the golden snail has been done in the En-tomological Laboratory of Medicinal and Aromatic Crops Research Institute, Bogor, Indonesia from February to October 2008. The study used factorial ith rando-mized block design basis. The first factor is three levels dipping time of 5, 10, and 20 hours. The second factor is 14 kinds of extracts to be tested i.e. extracts of clove, the crown of god, seraiwangi, turmeric, physic nut, pig nut, legundi, chili java, ba-badotan, brotowali, bitter, kenikir, noni, and rerak. Research initially conducted by dissolving 5% tween 80 in water. After that into the 1 l of solution is placed 5 g of extract to be tested so that the concen-tration of extract in the solution to be tested is 0.5%. After that the snails were put into the solution and were fed with ta-ro leaf (Colocasia giganteum). In the con-trol treatment the snail only be soaked in water containing 5% tween 80. Soaking performed for 5, 10, and 20 hours in glass jars 9 x 15 cm2 diameter. After soaking snails then were transferred into the bottle containing clean water and then given a taro leaf size 100 cm2 as food. Each tre-atment used 10 snails and repeated 3 times. Observations were made at 1, 2, and 3 days after application of the golden snail mortality by counting the number of snails that died after treatment and of inhibition of eating by noting the eaten leaf area. The results showed that the clove, the crown of god, Cintronella oil, and tur-meric are the most effective extract with 100% mortality rate and percentage of >90% inhibition of eating. Among the plants tested, clove most prospective to be developed as a controlling golden snail due to its high yield and the most immediate cause of death of the snail test.Â